(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
materials such as reinforced concrete and Portland cement. The development of net zero carbon buildings has become essential to reduce environmental impact and promote sustainable construction practices. Cold Formed Steel (CFS) and Highly Sulphated Calcium Silicate Cement (HSCSC) are emerging as low-carbon construction materials that offer improved structural efficiency and reduced carbon emissions. This study explores the integration of CFS structural systems with HSCSC-based concrete to develop net zero carbon building solutions. CFS provides lightweight and high-strength structural framing, while HSCSC significantly reduces carbon emissions compared to ordinary Portland cement. The research focuses on material properties, structural performance, and carbon emission reduction potential in building construction. A sustainable framework is proposed to evaluate energy efficiency, material optimisation, and carbon footprint reduction. The results indicate that the combined use of CFS and HSCSC can significantly lower embodied carbon, improve construction efficiency, and support net zero carbon building development. The study highlights the potential of advanced materials and innovative construction methods in achieving environmentally sustainable and energy-efficient buildings.